PEMBINAAN KEAGAMAAN DAN EKONOMI BAGI MUALAF OLEH DEWAN DAKWAH ISLAMIYAH INDONESIA DI LAMPUNG - Rini Setiawati; Khomsahrial Romli (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
Converts are people who are new to Islam and do not understand much about Islam. They need guidance regarding Islamic teachings. DDII (Dewan Dakwah Islam Indonesia) Lampung through the Laznas Council of the Da'wah Board of Trustees who are